2010
DOI: 10.1021/ic101708y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Diaryl Telluroxides and Tellurones by Photosensitized Oxygenation of Diaryl Tellurides

Abstract: Aerobic oxygenation of diaryl tellurides under photosensitized conditions is investigated. Unlike Ph(2)S and Ph(2)Se, reaction of diaryl tellurides with singlet oxygen proceeds smoothly to yield diaryl telluroxides and the corresponding tellurones. The product distribution is largely affected by the substrate and the reaction conditions. In particular, the photooxygenation of bulky diaryl tellurides principally produces tellurones. The results of a series of trapping experiments suggest that the diaryl telluro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…The three corresponding series of peri ‐substituted aryl tellurides were prepared from diaryl ditellurides bis(4‐fluorophenyl) ditelluride (FpTeTeFp), bis(4‐methylphenyl) ditelluride (TolTeTeTol), bis(4‐methoxyphenyl) ditelluride (An‐ p TeTeAn‐ p ), bis(2‐methoxyphenyl) ditelluride (An‐ o TeTeAn‐ o ), bis(4‐tertbutylphenyl) ditelluride (TpTeTeTp), bis(2,4,6‐trimethylphenyl) ditelluride (MesTeTeMes) and bis(2,4,6‐triisopropanylphenyl) ditelluride (TipTeTeTip) 15. Naphthalenes N2 – N8 were prepared by following the same procedure to that previously reported for the synthesis of 1,8‐bis(phenyltelluro)naphthalene N1 ;12 under an oxygen‐ and a moisture‐free nitrogen atmosphere, 1,8‐diiodonaphthalene was independently treated with two molar equivalents of n ‐butyllithium in diethyl ether to afford the precursor 1,8‐dilithionaphthalene, which when reacted with the appropriate diaryl ditelluride afforded N2 – N8 in moderate to good yield (yield: 65 ( N2 ), 13 ( N3 ), 45 ( N4 ), 15 ( N5 ), 51 ( N6 ), 11 ( N7 ), 26 % ( N8 ); Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The three corresponding series of peri ‐substituted aryl tellurides were prepared from diaryl ditellurides bis(4‐fluorophenyl) ditelluride (FpTeTeFp), bis(4‐methylphenyl) ditelluride (TolTeTeTol), bis(4‐methoxyphenyl) ditelluride (An‐ p TeTeAn‐ p ), bis(2‐methoxyphenyl) ditelluride (An‐ o TeTeAn‐ o ), bis(4‐tertbutylphenyl) ditelluride (TpTeTeTp), bis(2,4,6‐trimethylphenyl) ditelluride (MesTeTeMes) and bis(2,4,6‐triisopropanylphenyl) ditelluride (TipTeTeTip) 15. Naphthalenes N2 – N8 were prepared by following the same procedure to that previously reported for the synthesis of 1,8‐bis(phenyltelluro)naphthalene N1 ;12 under an oxygen‐ and a moisture‐free nitrogen atmosphere, 1,8‐diiodonaphthalene was independently treated with two molar equivalents of n ‐butyllithium in diethyl ether to afford the precursor 1,8‐dilithionaphthalene, which when reacted with the appropriate diaryl ditelluride afforded N2 – N8 in moderate to good yield (yield: 65 ( N2 ), 13 ( N3 ), 45 ( N4 ), 15 ( N5 ), 51 ( N6 ), 11 ( N7 ), 26 % ( N8 ); Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that diphenyl selenide ( 1a ) reacts with a 10‐fold excess amount of hypochlorite to produce diphenyl selenone ( 2a ) in 79 % yield 24. This result, however, could not be replicated by others 25. We treated 1a at 0 °C for 3 min with HOF · CH 3 CN (2.4 equiv., slight excess, as each equivalent is a source of one oxygen atom) to form Ph 2 SeO 2 ( 2a ) in quantitative yield.…”
Section: Resultsmentioning
confidence: 86%
“…Theu se of tellurium in fluorescent redox probes was inspired by results indicating diaryl tellurides undergo selective and rapid oxidation with singlet oxygen in the presence of as ensitizer. [68] Thef irst reported telluriumcontaining redox sensor was 2Me TeR, in which the xanthene O10 of rhodamine was replaced with tellurium, thus giving an onfluorescent molecule as ar esult of the heavy-atom effect. [43] Theo rganotellurium center was shown to be oxidized by the hydroxyl radical (COH), peroxynitrite (ONOO À ), and hypochlorite (OCl À )t og ive the corresponding telluroxide,which emits in the near-IR.…”
Section: Telluridesmentioning
confidence: 99%